9.3k views
2 votes
Consider the sequence of steps to solve the equation: 3(x - 4) + 5x 9x - 36

Given => 3(x-4)+ 5x 9x - 36
Step 1 = 3x - 12 + 5x-9x - 36
Step 2 -> 3x + 5x - 12-9x - 36
Step 3 8x - 12 - 9x - 36
Step 48x - 8x - 12 - 9x - 8x - 36
Step 5 => 0 - 12 - x - 36
Step 6-12 - 36
Step 7-12 + 36 x - 36 + 36
Step 8 = 24 x +0
Step 9 = 24 - x
Which property yields Step 1?
3)
A)
Distributive Property
B)
Multiplicative Identity
Multiplication Property of Equality

User Erickg
by
4.8k points

1 Answer

3 votes

Answer:

Distributive Property

Explanation:

You are distributing 3 to x and -4

User Artem Petrov
by
4.4k points